STUDI KOMPARASI MINAT MENABUNG PEDAGANG PASAR RAYA MEKONGGA PADA BANK BRI DAN BANK MUAMALAT KOLAKA. PERGRAM STUDI PERBANKAN SYARIAH FAKULTAS EKONIMI DAN BISNIS ISLAM, IAI AL MAWADDAH WARRAHMAH KOLAKA - Ahmad Syuaib Rahman; Amir Sahaka; Muh Iqbal (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
The economic activities of a country are always related to the flow of money payments, where the banking industry has a very strategic role, namely as the lifeblood of the economic system. Bank BRI is a bank that carries out activities based on conventional principles as a whole. Meanwhile, Bank Muamalat Indonesia is a bank that contains elements of sharia. The Kolaka area which is strategic and the community has various sources of income, which is very appropriate for running a business.The formulation of the problem in this study is how the interests of the traders of the mekongga highway in saving at Bank BRI and Bank Muamalat, how is the savings management system at Bank BRI and Bank Muamalat. The aim of this research is to find out how the interest in saving the traders of the Pasar Raya Mekongga bank BRI Kolaka and Bank Muamalat Kolaka. To compare the savings fund management system at Bank Bri and Bank Muamalat.The research method used is qualitative research. The object of research is Market Traders and the subject of the research is the interest of the Mekongga highway market at BRI Bank and Muamalat Kolaka. The research procedure used includes 3 stages, namely observation, interview and documentation.The results of the study show that the people's interest in saving is more likely to choose BRI Bank because the service is easy and not complicated, while those who save at Bank Muamalat are their reasons because they are avoiding the Riba system (especially Muslims) by using 2 systems, namely Wadiah and Mudharabah.